1988
DOI: 10.1152/ajprenal.1988.254.4.f470
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor-induced changes in renal blood flow: role of prostaglandins and histamine

Abstract: The role of histamine (H) and prostaglandins (PGs) in the renal vasoconstriction prompted by a 10-min intrarenal infusion of norepinephrine (NE, 0.2 micrograms), antidiuretic hormone (ADH, 10 mU), or angiotensin II (ANG II, 0.05 micrograms) was evaluated in anesthetized dogs (amounts are per min per kg). Renal blood flow (RBF, flow probe) decreased four- to fivefold during the 1st min of infusion with each agonist but then gradually returned toward base line. This "escape" was greatest with ADH, less with NE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…ERBF and ERPF during MRAP increased by the vasopressor infu sion of PEP and with paired hematocrit in creases of 10.1 ± 1.6% represent evidently renal circulatory autoregulation as a com bined function of both MRAP and hemato crit change occurring simultaneously. This finding of renal hemodynamic constancy, was apparently in association with the renal blood flow escape phenomenon from a renal a-adrenergic vasoconstrictor effect, an es cape recently described by Banks [60] with norepinephrine.…”
Section: Discussionsupporting
confidence: 58%
“…ERBF and ERPF during MRAP increased by the vasopressor infu sion of PEP and with paired hematocrit in creases of 10.1 ± 1.6% represent evidently renal circulatory autoregulation as a com bined function of both MRAP and hemato crit change occurring simultaneously. This finding of renal hemodynamic constancy, was apparently in association with the renal blood flow escape phenomenon from a renal a-adrenergic vasoconstrictor effect, an es cape recently described by Banks [60] with norepinephrine.…”
Section: Discussionsupporting
confidence: 58%
“…The role of PG in attenuating the renal vasoconstriction induced by NE has been proposed in studies showing that 1) NE increases the production of PG in the kidney (6,15); 2) COX inhibition leads to a marked potentiation of NE-induced renal vasoconstriction (1,2,15); and 3) PG infusion attenuates the renal vasoconstriction elicited by NE (3,14). Some results reported in the aforementioned previous studies have been confirmed in our study, because we have found that intrarenal infusion of NE enhances the urinary excretion of PGE 2 and 6-keto-PGF 1␣ and that the renal hemodynamic effects of NE are potentiated by the infusion of a nonselective COX inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…renal function; glomerular filtration rate; renal vascular resistance; prostaglandins; cyclooxygenase-2 IT IS WELL KNOWN THAT ENDOGENOUS prostaglandins (PG) play an important role in regulating renal function when vasoconstrictor levels are elevated (1-3, 6, 14, 15, 18, 22). This notion is supported by studies showing that norepinephrine (NE) infusion induces an increment in renal synthesis of PG (5,15) and that the renal vasoconstriction induced by NE is significantly potentiated when synthesis of PG is reduced (1,2,15). Finally, it has been reported that PGI 2 infusion reduces the renal vasoconstriction elicited by NE (3,14).…”
mentioning
confidence: 89%
“…This appears to be a compensatory phenomenon in low-flow vasoconstrictive states such as hypovolemic shock, as shown by previous studies in our laboratory [2], in which higher plasma levels of histamine were dem onstrated in surviving than in nonsurviving animals. Ischemia of single organs is also associated with the release of histamine [3,4].…”
Section: Introductionmentioning
confidence: 99%